SOC estimation of lithium battery based on extended Kalman filter algorithm - Cui Gengtao; Jiang Weihua; Tu Wei (Dianzi Jishu Yingyong, 2021)
In the battery management system, the accurate estimation of State of Charge(SOC) has an important position, its impor- tance is not only to the user prompt battery remaining power, more is that it is the basis of the battery charge and discharge management and balanced control management.And SOC is affected by many factors, such as temperature and current size,direction,etc,so it is difficult to predict it accurately.In this paper, an extended Kalman filter(EKF) algorithm is proposed to estimate the SOC of lithium battery.The battery model was established, and the parameter identification was carried out through the Hybrid Pulse Power Characteristic(HPPC) test.The SOC estimation error of the model is about 2.1% under constant discharge,it shows that the model is effective and easy to apply.